Introducing .NET 4.0 With Visual Studio 2010 - Mackey, Alex (Apress, 2012)
Many developers are too busy (or lazy!) to learn new technologies and skills. This is a shame, as they miss out on • Producing better software • Making their lives easier through better and easier-to-maintain code • Opening up new promotion and job opportunities • Impressing people First of all, let’s get out of the way what this book is not… This book is about breadth rather than depth, so it may not cover some areas in as much detail as you would want. Secondly, this book is written for the professional edition of Visual Studio 2010, so we will not be covering some of the great new features available in Premium and Ultimate editions of Visual Studio. It’s not that these features are not important—it’s more that I believe the majority of developers utilize the professional edition and there’s more than enough to cover already.